CRISIS COMMUNICATIONS MANAGEMENT IN APARTMENT RESIDENCE: HOW THE PUBLIC RELATIONS OFFICERS HANDLE CONFLICT BETWEEN MANAGEMENT AND TENANT - Irmulansati Jauhari Tomohardjo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
The five main strategies are rejection, avoiding responsibility, reducing attacks, corrective actions, and self-recognition. The research method used is a qualitative case study. Researchers conducted in-depth interviews with four informants, namely to the public relations officer of Jakarta Apartments, legal experts, apartment residents, and communication experts. Researchers will retrieve data from the four speakers related to the problem between Jakarta management and one of tenant. From the results of research based on the results of interviews that researchers have described, researchers see that the strategy undertaken by the manager of the Jakarta apartment is more dominant on how to reduce attacks from the public when the crisis peaks. The manager applies this strategy through social media with digital listening which answers every customer complaint and corrects any incorrect things related to Jakarta. The management also implemented a self-recognition strategy by apologizing due to the crisis that had occurred. Based on the statement of the communication expert, this is very rare. Usually for a company, the word sorry is rarely said when experiencing a crisis. The shortcomings of the strategy adopted are the way the crisis is overcome itself that should apply consumer relations and approach consumers. This is not done by the manager of Jakarta Apartments case of SP3 letters that have not been revoked from Mr X as residents, according to the manager it is not the authority of the manager but the police. Make corrections to each complaint from customers and also in terms of service. The rest, the management focuses on strategies to reduce attacks from residents and also the public who already have a negative perception of the manager of the Jakarta Apartments.